2013
DOI: 10.3989/gya.049113
|View full text |Cite
|
Sign up to set email alerts
|

Development of a zero <i>trans</i> margarine from soybean-based interesterified fats formulated using artificial neural networks

Abstract: The formulation of products with low levels of saturated and trans fatty acids is a new challenge for industries, and alternative raw materials have been studied. Artificial neural networks (ANNs) have been used for this process. The objective of the present study was to formulate blends, with the help of an ANN, using soybean-based interesterified fats for the production of a zero trans fat margarine similar to a margarine produced using a specific commercial fat. The software was trained with three ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 14 publications
0
9
0
3
Order By: Relevance
“…Garcia et al (2013) also showed that neural networks were highly efficient in predicting the solid fat content and the melting point of blends elaborated with soybean-based interesterified fats. Table 1 shows the theoretical fatty acid composition of the formulated blends, as well as the amounts of saturated, monounsaturated, polyunsaturated and trans fatty acids.…”
Section: Characterization Of the Blendsmentioning
confidence: 95%
See 2 more Smart Citations
“…Garcia et al (2013) also showed that neural networks were highly efficient in predicting the solid fat content and the melting point of blends elaborated with soybean-based interesterified fats. Table 1 shows the theoretical fatty acid composition of the formulated blends, as well as the amounts of saturated, monounsaturated, polyunsaturated and trans fatty acids.…”
Section: Characterization Of the Blendsmentioning
confidence: 95%
“…Moreover, the controversy about the effects of the consumption of trans fatty acids for human health represents a challenge, with companies being required to produce fats and shortenings with reduced formation of trans fatty acids (Garcia et al, 2013), healthier formulations that present the same functionality and economic viability, with a reduced amount of saturated fatty acids (Ribeiro et al, 2007;Dhaka et al, 2011;Doan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address the shortcomings of chemical interesterification, recent studies have reported the organogel technology as an unconventional method for structuring lipid bases of plant origin (Chaves, Barrera-Arellano, & Ribeiro, 2018;Garcia, Gandra, & Barrera-Arellano, 2013;Marangoni & Garti, 2011). Organogels are semi-solid systems, in which the oil phase is imprisoned by a self-sustained three-dimensional network of the structuring agent.…”
Section: Lipid Modification Processesmentioning
confidence: 99%
“…However, although many of the currently used raw materials do not contain TFAs, they are rich in saturated fatty acids. Saturated fatty acids are also considered detrimental to human health, as they are known to contribute to an increased risk of cardiovascular disease [1,2].…”
Section: Introductionmentioning
confidence: 99%